TNM classification and the need for revision of pN3a breast cancer. (July 2017) - van Nijnatten, T.J.A.; Moossdorff, M.; de Munck, L.; Goorts, B.; Vane, M.L.G.; Keymeulen, K.B.M.I.; Beets-Tan, R.G.H.; Lobbes, M.B.I.; Smidt, M.L.
Abstract: Background: According to the seventh edition of tumour-node-metastasis (TNM) classification, pN3a status in breast cancer patients consists of presence of an infraclavicular lymph node metastasis (LNM) and/or presence of ≥10 axillary LNMs. The aim of this study was to determine whether prognosis of pN3a based on at least an infraclavicular LNM differs from ≥10 axillary LNMs. Methods: Data were obtained from the Netherlands Cancer Registry. All patients were diagnosed between 2005 and 2008 with primary invasive epithelial breast cancer and pN2a or pN3a status as pathologic result. Patients with pN3a were subdivided in pN3a based on at least an infraclavicular LNM or ≥10 axillary LNMs. Disease-free survival (DFS) included any local, regional or contralateral recurrence, distant metastasis or death within 5 years. Kaplan–Meier curves provided information on 5-year DFS and 8-year overall survival (OS). In addition, Cox proportional hazards model was used to measure the effect of relevant clinicopathological variables on DFS and OS. Results: A total of 3400 patients with pN2a and 1788 patients with pN3a were included. In 83 patients, pN3a was based on at least an infraclavicular LNM (4.6%) and in 1705 patients because of ≥10 axillary LNMs (95.4%). After multivariable analyses, DFS and OS were inferior in patients with pN3a based on ≥10 axillary LNMs compared to infraclavicular LNM (DFS 48.8% versus 63.8%, hazard ratio [HR] 1.59, p = 0.036; OS 46.6% versus 63.9%, HR 1.46, p = 0.042). Furthermore, pN2a and pN3a based on infraclavicular LNM had comparable DFS and OS. Conclusion: PN3a status based on an at least an infraclavicular LNM is rare, yet its prognosis is superior to ≥10 axillary LNMs. Reclassification of infraclavicular LNM in the next TNM should therefore be considered into pN2a. Highlights: Breast cancer nodal status comprises number and location of lymph node metastases. pN3a consists of infraclavicular and/or ≥10 axillary lymph node metastases. Prognosis of an infraclavicular lymph node metastasis is superior to ≥10 axillary. Revision of infraclavicular lymph node metastases is advised in the next TNM.